Detection and identification of Foot and Mouth disease virus serotypes in Assiut governorate, Egypt - El-Khabaz, Khaled Ahmed Sayed; Al-Hosary, Amira Adel Taha (Journal of Advanced Veterinary and Animal Research, 2017)
Objective: Molecular based study was conducted to determine the associated serotypes in the reemergence of Foot and Mouth Disease (FMD) outbreak in Assiut governorate, Egypt during 2014 and 2015. Materials and methods: One hundred and twenty cattle with clinical signs suggesting their infection by FMDV were examined clinically and twenty three of them were used for confirmation by laboratory diagnosis. Different clinical samples including vesicular fluid and tongue epitheliums were collected and after RNA extraction using commercial kit, RT-PCR was done using different primer sets. Results: Serotype O was detected in 8 samples, 2 of them were also positive for SAT2 serotype. The determination of specific serotype was failed in case of the rest 13 samples although they were positive when tested by the universal primer specific for FMDV. Conclusion: Serotypes O and SAT2 were the more prevalent serotypes in the current outbreak in Assiut governorate, Egypt. http://doi.org/10.5455/javar.2017.d186